Public use management in protected areas: laying the way for a new research trail in post pandemic Costa Rica - Mayorga Castro, Marisol (Kansas State University, 2022)
Costa Rica protects almost 30% of its territory and holds nearly 6% of the world’s biodiversity in just 0.03% of the Earth’s surface. Considered for decades a “green republic,” its long tradition of conservation, political stability, democracy, anti-militarism, and strategic location between two oceans and proximity to the North American market, helped the country to position itself as a worldwide model for ecotourism in the 1990s. Since then, tourism has been the most important engine of economic development for Costa Rica (even during the pandemic), and visitation has steadily increased, especially to protected areas. Park managers, then, uphold a triple mandate to preserve heritage, support surrounding communities in their enjoyment of benefits that derive from ecotourism, and at the same time guarantee that visitors achieve satisfying experiences. A principal pathway to the fulfillment of this mandate, particularly for visitor satisfaction and heritage protection, is effective tourism management, known as public use or visitor management. To monitor the effectiveness of such management, make improvements, or try new models, research is required. Unlike in the United States which enjoys a long tradition of public use and recreation research professionals and institutions, Costa Rica has no strategy or even recognizes the little public use management research which has taken place within its borders. The first part of this dissertation identifies existing publications and research gaps about public use management in Costa Rica’s national protected areas system. Also, it highlighted the most urgent public use management research needs and interests reported by park managers and other protected area stakeholders in Costa Rica. Based on these findings, a research agenda was designed to guide future public use management research in the country, and in particular for the Paraíso and Turrialba region, the area of influence of the University of Costa Rica-Paraiso Branch, where the author works with the Ecological Tourism Program. Additionally, both to illustrate the use of this new research agenda and to begin to fill in one of the identified gaps, a case study was developed to identify underlying factors that influence the visitor’s perception of the authenticity of Guayabo National Monument, an archeological site located within a forest and one of Costa Rica’s most important cultural heritage sites. This research employed mixed methods and tools: a literature review and synthesis, personal interviews, and template analysis were applied to identify existing publications and gaps in public use management research, and for the development of the research agenda. An online survey identified social science research needs in protected areas, and for the perception of authenticity, an on-site survey and Exploratory Factor Analysis (EFA) were applied. The results produced, for the first time in Costa Rica, an updated database of existing publications and a research agenda to guide future public use management research. The EFA generated a set of factors that related to a framework by Wang (1999) in which he presented the concepts of objective, constructive, and existential authenticity. There are no other studies that have done this, and thus it will serve to develop a scale of visitor perception of authenticity in Guayabo National Monument which can later be tested and adapted to other protected areas. The implications for managers and researchers are important because once pandemic restrictions are lifted, visitation will surely surge. This post-pandemic era presents a unique opportunity to introduce new management actions along with more concerted research efforts that should strengthen the planning, monitoring, and improvement of public use management, hopefully, at the same time that visitor satisfaction and conservation also increase in Costa Rica.
Keywords: Costa Rica; Public use management; Visitor management; Protected areas; Authenticity; Heritage tourism